2013
DOI: 10.2147/jmdh.s46784
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes an excellent allied health care professional? A multidisciplinary focus group study

Abstract: BackgroundDetermining what constitutes an excellent allied health care professional (AHCP) is important, since this is what will guide the development of curricula for training future physical therapists, oral hygienists, speech therapists, diagnostic radiographers, and dietitians. This also determines the quality of care.AimTo describe perspectives of AHCPs on which characteristics are commonly associated with an excellent AHCP.MethodsAHCPs’ perspectives were derived from three focus group discussions. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Hoe kunnen docenten en studenten elkaar binnen het honoursonderwijs versterken, en is er sprake van een specifieke honoursdidactiek (Wolfensberger, 2012). Hoe kan de relatie versterkt worden tussen succes in de beroepspraktijk en het gevolgde (honours)onderwijs (Paans, Wijkamp, Wiltens, & Wolfensberger, 2013;Scager et al, 2012;Van Dijk, 2012) en hoe denken honoursalumni daarover (Wolfensberger, Sweijen, Van Eijl, Hartog, & Van der Vaart, 2010)?…”
Section: Uitdagingen Door De Tijd Heenunclassified
“…Hoe kunnen docenten en studenten elkaar binnen het honoursonderwijs versterken, en is er sprake van een specifieke honoursdidactiek (Wolfensberger, 2012). Hoe kan de relatie versterkt worden tussen succes in de beroepspraktijk en het gevolgde (honours)onderwijs (Paans, Wijkamp, Wiltens, & Wolfensberger, 2013;Scager et al, 2012;Van Dijk, 2012) en hoe denken honoursalumni daarover (Wolfensberger, Sweijen, Van Eijl, Hartog, & Van der Vaart, 2010)?…”
Section: Uitdagingen Door De Tijd Heenunclassified
“…Extant research on clinician competence has found that best practices include being cognizant, communicative, innovative, introspective, holistic in incorporating information from multiple sources (eg, clinicians, patients, families), and evidence-driven. [1][2][3] In this context, being evidence-driven ideally integrates knowledge from both rigorous empirical research and real-world, practice-based research (PBR), resulting in comprehensive evidence-based practice (EBP). 4 EBP is an evolving concept in the health professions.…”
Section: Introductionmentioning
confidence: 99%
“…14 As such, a framework for single-session practice competencies would be useful for social workers to further develop their skills and contributions to multidisciplinary teams. Experienced allied health clinicians are expected to further their professional competencies, 2 many of which are shared across disciplines. 15 , 16 Allied clinician activities in single sessions often include: conducting psychosocial assessments and interventions; providing supportive counseling for adjustment to illness; promoting health; and providing resources and referrals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-a sociogram reflecting the socially significant personality traits of a speech therapist. Nevertheless, studies that would consider not only psychological characteristics, but the psychophysiological aspect of professional readiness for speech therapist activity are not presented in the literature [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%